REKONSTRUKSIONISME DALAM PENDIDIKAN ISLAM: MENGHADAPI TANTANGAN AKSES INFORMASI DI ERA DIGITAL: (Reconstructionism in Islamic Education: Facing the Challenges of Information Access in the Digital Era) - Adila Jian Nevira; Mhd. Zikri Nasution; Nur Sa’adah; Herlini Puspika Sari (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
Islamic education plays a central role in shaping character and developing the full potential of individuals, particularly in striving to fulfill the purposes of life as servants of Allah and stewards on earth. Despite undergoing various changes from the colonial era to the independence period, Islamic education in Indonesia still faces challenges, including the dichotomy of education, curriculum, and management that are often considered inconsistent and lacking clear direction. With a reconstructionist approach, which prioritizes the transformation of the education system to be relevant to modern social and cultural conditions, efforts can be made to reform Islamic education to address these fundamental issues. In the era of Society 5.0, where the physical and virtual worlds are increasingly interconnected through IoT and artificial intelligence, Islamic education is confronted with both new opportunities and challenges. This era demands a transformation in teaching methods that not only leverage technology but also uphold moral and character values. This paper aims to assess the readiness of Islamic education in facing the era of Society 5.0 with a reconstructionist approach as a new paradigm to optimize information access and align education with contemporary needs